Seasonality and community interventions in a mathematical model of Clostridium difficile transmission. Issue 2 (June 2019) - McLure, A.; Furuya-Kanamori, L.; Clements, A.C.A.; Kirk, M.; Glass, K.
Summary: Background: Clostridium difficile infection (CDI) is the leading cause of antibiotic-associated diarrhoea with peak incidence in late winter or early autumn. Although CDI is commonly associated with hospitals, community transmission is important. Aim: To explore potential drivers of CDI seasonality and the effect of community-based interventions to reduce transmission. Methods: A mechanistic compartmental model of C. difficile transmission in a hospital and surrounding community was used to determine the effect of reducing transmission or antibiotic prescriptions in these settings. The model was extended to allow for seasonal antibiotic prescriptions and seasonal transmission. Findings: Modelling antibiotic seasonality reproduced the seasonality of CDI, including approximate magnitude (13.9–15.1% above annual mean) and timing of peaks (0.7–1.0 months after peak antibiotics). Halving seasonal excess prescriptions reduced the incidence of CDI by 6–18%. Seasonal transmission produced larger seasonal peaks in the prevalence of community colonization (14.8–22.1% above mean) than seasonal antibiotic prescriptions (0.2–1.7% above mean). Reducing transmission from symptomatic or hospitalized patients had little effect on community-acquired CDI, but reducing transmission in the community by ≥7% or transmission from infants by ≥30% eliminated the pathogen. Reducing antibiotic prescription rates led to approximately proportional reductions in infections, but limited reductions in the prevalence of colonization. Conclusion: Seasonal variation in antibiotic prescription rates can account for the observed magnitude and timing of C. difficile seasonality. Even complete prevention of transmission from hospitalized patients or symptomatic patients cannot eliminate the pathogen, but interventions to reduce transmission from community residents or infants could have a large impact on both hospital- and community-acquired infections.